The Results of Local Steroid and Physiological Saline Solution Used for Chronic Achilles Tendinitis, A 2-Year Follow Up, - Kılıç, B., Zekioğlu, A., Yücel, A. S., (My University, 2014)
Background and objectives: Achilles tendon (AT) is the strongest and the thickest tendon of human body. Sarcostyles of this tendon are not exactly vertical and have a spiral shape to some extent. Due to this fact, tendon gets stronger and the contact (friction) between sarcostyles decreases. Achilles tendinitis is a kind of wounding that can be caused by overuse or misuse of achilles tendon, lack of flexibility, genetical structure, gender, age, height, weight, pes cavus deformity, lateral ankle instability, forefoot varus, lateral heel throb during the act of walking and excessive compensatory pronation, decrease in ankle dorsiflexion, lower extremity alignment disorders, endocrine and some metabolic factors and many others. It mostly happens for athletes. If we look with a histopathological perspective at achilles tendinitis, we will see that tendon has an angiofibroblastic hyperplasia. The reaction created against the degenerative process of tendon is an inflammatory response in peritenon. Throughout the treatment, pains and tenderness are tried to be decreased. In order for this purpose, resting, hypothermia and NSAID can be applied. Raising the heel is recommended in order to decrease the burden on tendon. Within the chronic process, the renewal of tendon is preferred. Methods: In our study; a 30 cc local anesthetic and saline physiological injection was applied to 38 of 98 patients while a mixture of 15 cc corticosteroid and local anesthetic injection was applied to 60 patients. Conclusion: It is highly significant that we did not record any relapse within our 2-year follow-up after increasing local blood circulation with the injection of physiological saline and local anesthetic mixed solution although we got the response later than steroid method and the rate of success in this method was relatively low. Moreover, this method has no side effects and can be used securely when steroid method cannot be used.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Achilles Tendon; Tendinitis; Local Steroid